PERANAN KELUARGA DALAM PENDIDIKAN KARAKTER ANAK PADA PEMBELAJARAN PKN DI MIN 12 MEDAN - Savira Maharani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to analyze the role of the family, the type of character developed, approaches, factors that play a role, obstacles, and efforts in overcoming character education of elementary school children in the family. This research was conducted at MIN 12 Medan by using qualitative approach and descriptive method. The results refer to first, the role of mothers is more dominant than the role of fathers in educating the character of elementary school children. Second, the characters developed include independence and responsibility. Third, the approaches taken in elementary school children's character education are 1) affection, 2) advice, 3) discipline, 4) exemplary, 5) habituation, and 6) the use of electronic media. Fourth, the factors that play a role include internal and external family factors. Fifth, the obstacles that occur in elementary school children's character education are the social and emotional development of children who have not developed optimally. Sixth, the efforts made to overcome obstacles in character education include affection and advice approaches which are the most dominant efforts made by families to children.